Helicobacter pylori risk in type 2 diabetes mellitus: a hospital based case-control study - S., Rajesh; S., Reshma; Kamal V., Shruthi (International Surgery Journal, 2017)
Background: The aim of this study is to determine the frequency of Helicobacter pylori (H. pylori) infection in Type 2 diabetic and non-diabetic patients with dyspeptic symptoms and to compare the frequency of H. pylori infection in both groups. Methods: This was a hospital-based case-control study was conducted on 196 subjects in the Department of General Surgery, Saveetha Medical College and Hospital (tertiary care hospital) from March 2016 to November 2016. Patients were divided into two groups i.e. type 2 diabetics with poor glycemic control with dyspeptic symptoms and non-diabetics with dyspeptic symptoms. Each group consisted of 98 patients. All type 2 diabetic patients of ≥35 years of age with poor glycemic control both gender and the known cases with history of dyspepsia, epigastric pain or bloating for more than a month were screened for helicobacter pylori infection. The collected data of both groups was evaluated and separated for analysis Results: Majority of the patients were male with mean age±SD, 50±12. Among the type II diabetic group with dyspeptic symptoms, H. pylori was positive in 70/98 (71.4%), whereas in non-diabetic group with dyspeptic symptoms H. pylori was positive in 51/98 (52%) cases. Conclusion: Type II diabetic patients with dyspeptic symptoms are more prone and at risk to acquire H. pylori infection. Therefore, proper monitoring of blood glucose level and screening for H. pylori infection are effective preventive measures for this chronic infection.